1991
DOI: 10.1007/bf00982120
|View full text |Cite
|
Sign up to set email alerts
|

Fumigant toxicity of essential oils against four major stored-product insects

Abstract: The fumigant toxicity of 28 essential oils extracted from various spice and herb plants and some of their major constituents were assessed for adult coleopteransRhyzopertha dominica, Oryzaephilus surinamensis, Tribolium castaneum, andSitophilus oryzae. Three groups of active materials were distinguished: (1) The compounds terpinen 4-ol, 1,8-cineole, and the essential oils of three-lobed sage, sage, bay laurel, rosemary, and lavender were most active againstR. dominica; (2) The compounds linalool,α-terpineol, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
141
0
13

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(161 citation statements)
references
References 2 publications
7
141
0
13
Order By: Relevance
“…Essential oils of spices and their constituents have also been reported as a potent source of botanical pesticides (Singh and Upadhyay 1993). The essential oils of several spices like anise (Pimpinella anisum L.) and peppermint (Mentha piperita L.) have been found to have fumigant toxicity to four major stored product pests, R. dominica, Tribolium castaneum (Herbst), S. oryzae and Orzyaephilus surinamensis (L.) (Shaaya et al 1991). Ho et al (1996) found that the essential oil of garlic is insecticidal to T. castaneum and Sitophilus zeamais Motschulsky.…”
Section: Resultsmentioning
confidence: 99%
“…Essential oils of spices and their constituents have also been reported as a potent source of botanical pesticides (Singh and Upadhyay 1993). The essential oils of several spices like anise (Pimpinella anisum L.) and peppermint (Mentha piperita L.) have been found to have fumigant toxicity to four major stored product pests, R. dominica, Tribolium castaneum (Herbst), S. oryzae and Orzyaephilus surinamensis (L.) (Shaaya et al 1991). Ho et al (1996) found that the essential oil of garlic is insecticidal to T. castaneum and Sitophilus zeamais Motschulsky.…”
Section: Resultsmentioning
confidence: 99%
“…This method is convenient and inexpensive for the protection of stored seeds in households and on small farms (SHAAYA et al 1997). Essential oils have a low toxicity to warm-blooded animals, high volatility, and toxicity to stored-grain insect pests (REGNAULT-ROGER & HAMRAQUI 1993;SHAAYA et al 1991). This paper reports the toxicity of Khaya senegalensis (Desv.)…”
mentioning
confidence: 99%
“…The oils of Oregano, Basil, de Marjoram, Thyme, Sage, Laurier, Rosemary, Lavender, Anise, Mint, Celery, Cumin, Citrus Fruit, Coriander and de Fennel have been tested and several have caused up to 100 % of mortality in the small borer of cereals, Rhysopertha dominica (F.), the saw-toothed grain beetle, Oryzaephilus surinamensis (L.), the red flour beetle, Tribolium castaneum (Hbst.) and the rice weevil (Shaaya et al, 1991). …”
Section: Discussionmentioning
confidence: 99%